Development of WSN air quality sensing nodes and sensor network - Hu, JunHao (2014)
This report summarizes the setting up of Raspberry pi server for data collection and storage. Incorporating with the sensor nodes, temperature, pressure, humility, altitude and airflow can be monitor and analyze. The setting up of server is done, with a number of tests completed on the sensor network. Additional features are completed that include the battery level monitoring and power efficiency when nodes are not in use.